1998
DOI: 10.1029/98gl02565
|View full text |Cite
|
Sign up to set email alerts
|

Europa's surface composition and sputter‐produced ionosphere

Abstract: Abstract. The efficient sputtering and decomposition of Europa's regolith by energetic charged particles produces an atmosphere representative of its surface composition. In addition to 02 and H2 from the decomposition of ice, we show that molecules representative of organics and salts will be present in ionic form at levels detectable using an ion mass spectrometer on an orbiting spacecraft. Such an instrument can also measure isotope ratios to determine surface age.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
50
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 62 publications
(50 citation statements)
references
References 41 publications
0
50
0
Order By: Relevance
“…One may be tempted to conclude that the impact of energetic ions from the magnetosphere of Jupiter is needed to sputter water and other molecules from the surface to create a neutral atmosphere [cf. Cooper et al, 2001;Johnson and Leblanc, 2001;Johnson et al, 1998] to be accompanied by photoionization to create an ionosphere. However, we feel that it is dangerous to speculate much beyond the facts, namely that detectable ionospheres were only observed when the ramside was sunlit.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One may be tempted to conclude that the impact of energetic ions from the magnetosphere of Jupiter is needed to sputter water and other molecules from the surface to create a neutral atmosphere [cf. Cooper et al, 2001;Johnson and Leblanc, 2001;Johnson et al, 1998] to be accompanied by photoionization to create an ionosphere. However, we feel that it is dangerous to speculate much beyond the facts, namely that detectable ionospheres were only observed when the ramside was sunlit.…”
Section: Discussionmentioning
confidence: 99%
“…First, by analogy with Europa, it is reasonable to assume that the neutral atmosphere consists primarily of O 2 formed from dissociation of H 2 O sputtered from Callisto's surface [Hall et al, 1995;Johnson et al, 1998]. …”
Section: Discussionmentioning
confidence: 99%
“…Graphitecompounds could be created through radiation bombardment and surface chemistry [Lifshitz et al, 1990;McCord et al, 1998], which could produce C − 2 . Sputtering experiments indeed predict the efficient production of the C2H − x anions from hydrocarbon compounds [Johnson et al, 1992], and these are suggested as candidate sputter products at Europa [Johnson et al, 1998]. Carbon chain anions have also possibly been observed at Comet Halley [Cordiner & Charnley, 2014] and exist elsewhere in Saturn's magnetosphere, amongst carbon-rich compounds in Titan's ionosphere [Desai et al, 2017a].…”
Section: Origin Of the Negative Ionsmentioning
confidence: 99%
“…This is important as radiolysis is a dominant surface alteration process on outer solar system bodies including those in the Kuiper belt and the Oort cloud. Having an accurate model can also be helpful for predictions, since Europa's atmosphere is expected to contain other interesting, possibly organic, molecules sputtered from the surface (Johnson et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…This is important as radiolysis is a dominant surface alteration process on outer solar system bodies including those in the Kuiper belt and the Oort cloud. Having an accurate model can also be helpful for predictions, since Europa's atmosphere is expected to contain other interesting, possibly organic, molecules sputtered from the surface (Johnson et al, 1998).The plasma interaction with the surface is the principal source of 02, and the plasma interaction with the atmosphere is a principal loss process, and therefore a large atmosphere does not accumulate ( Johnson et al, 1982). Ip (1996) modeled the atmosphere using the sputtering rates estimated by Shi et a1.…”
mentioning
confidence: 99%